Policy Convergence under Decentralization: Lessons from Indonesia’s Response to the COVID-19 Pandemic - Gabriel Lele (Indonesian Association for Public Administration, 2023)
Research on policy convergence has developed very significantly in comparative literature. However, little is known about the dynamics of policy convergence under unitary systems, assuming that they have greater convergence than under federal systems. This research maintains that unitary systems present no less intricate dynamics of policy convergence than the federal systems. Looking at a decentralized unitary system, this research argues that the dynamics of policy divergence is primarily driven by a need to pursue responsiveness to local priorities. It assesses the case of Indonesia in responding to the COVID-19 pandemic through qualitative and quantitative exploration, combining documentary and the named entity recognition (NER) methods. The main data were sourced from the selected national newspapers sanctioned by the Indonesian Press Board. The result points to several factors affecting policy convergence, namely, responsiveness, compliance, policy inconsistency, policy clarity, leadership, horizontal learning, and electoral politics. Of these factors, the most important one is policy responsiveness; that is, whether national and subnational policies converge or diverge is affected by the need of a subnational government to respond to local priorities. This research fills the void in the current research by understanding the interplay between domestic factors and policy convergence, thereby extending the debate on the dynamic of policy convergence under a decentralized unitary system. Working with the COVID-19 pandemic adds nuances to the literature on crisis-driven policy convergence dynamics. It also points to a practical implication on the importance of crafting better institutional arrangements on national-subnational relations to better respond to pressing issues in a more convergent manner.